STRATEGI PENGHIMPUNAN DAN PENGEMBANGAN WAKAF UANG DI BADAN WAKAF UANG MUHAMMADIYAH SUMATERA BARAT - Afriyuda, Erik; Wira, Ahmad; Tiswarni, Tiswarni; Setiawan, Fadli (Smart Education, 2025)
Abstract: This research is motivated by the activities of the Muhammadiyah Cash Waqf Board (BWUM) of West Sumatra in both the collection and development of cash waqf funds. BWUM also serves as an active and professional nazhir (waqf manager) in managing these funds. The main research question is: what are the strategies employed by BWUM of West Sumatra in collecting and developing cash waqf, and what are the supporting and inhibiting factors in these processes? Based on the research findings, it is revealed that: a) the fundraising strategy used by BWUM West Sumatra follows a corporate fundraising approach. BWUM collaborates with wakif (waqf donors) to collect cash waqf funds through several partnerships, including with Muhammadiyah University of West Sumatra, BTM West Sumatra, and other parties such as stores, supermarkets, mosques, and offices. b) The strategy for developing cash waqf at BWUM West Sumatra involves two main approaches: first, direct investment in the real sector, such as organic catfish farming, sugarcane plantations, establishing a